Phenolic compounds in coconut (Cocos nucifera L.) endosperm - Baldiviano, Perla F.; Laurena, Antonio C.; Tecson-Mendoza, Evelyn Mae (1999)
The phenolic compounds content of liquid and solid coconut endosperms at three stages of maturity were quantitatively determined by three methods. The three types of phenolic compounds, total phenol content, vanillin-positive or flavan-type phenolics and protein-precipitating polyphenols or condensed tannins decreased during the maturation of solid endosperm: total phenols from 4.01 to 1.00 mg catechin/g dry sample or catechin equivalents (CE), flavan-type phenolics from 0.40 to 0.06 CE, and protein-precipitating polyphenols from 2.64 to 0.64 mg tannic acid/g dry sample or tannic acid equivalents (TAE). The phenolic content values obtained at three stages of maturity of coconut liquid endosperm were similar and 20-60 times lower than those of the solid endosperm.

Thin layer chromatography (TLC) of simple phenols showed that the phenolic composition profile changed with maturity. However, four phenolic bands were consistently present in all the three stages of coconut solid endosperm. One of these bands was identified as gentisic acid. For the liquid endosperm, the phenolic profiles were similar at the three stages. Of the 6 consistent phenolic bands, three were identified to be umbelliferone, p-coumaric acid and syringic acid.
Keywords: Coconut; Chemical properties